Perlindungan Hukum Pemegang Hak Atas Tanah terhadap Manipulasi Data dalam Sistem Sertifikat Elektronik: Analisis Tanggung Jawab Negara dalam Pencegahan Mafia Tanah - Satriani, Satriani (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Digital transformation in the land sector through the implementation of electronic certificates is part of the government's efforts to improve service efficiency, data security, and legal certainty over land rights. However, the development of electronic systems does not completely eliminate the possibility of land mafia practices, particularly those involving data manipulation and abuse of authority by parties with access to the land system. This study aims to analyze the forms of legal protection for land rights holders against data manipulation in the electronic certificate system and to examine the state's responsibility in preventing and addressing losses arising from such practices. This research uses a normative legal method with a statutory and conceptual approach. Legal materials were obtained through qualitative literature review. The results indicate that legal protection is provided through preventive mechanisms such as authentication systems, electronic signatures, audit trails, and land database security, as well as through repressive mechanisms such as certificate cancellation, civil lawsuits, lawsuits to the State Administrative Court, and criminal law enforcement. The state's responsibility is realized through the implementation of a secure, reliable, and accountable electronic system and strengthened internal oversight to prevent land mafia practices and ensure legal certainty for land rights holders.